Educação patrimonial e educação de jovens e adultos: uma experiência na Escola Marieta D` Ambrósio em Santa Maria/RS - Freitas, Neida Maria Camponogara de (2014)
Thinking of public school in the context of formal education, as the institution responsible for the basic training of most Brazilian citizens, it is important to approach the Heritage Education in the school curriculum. This study will focus the trend analysis of cultural freeholds which approach their relations with the identities and memories of a place, linked to the people who live there and enjoy the collective environments in their daily lives. It constitutes therefore an important link to the cultural formation of the individual related to the different realities, seeking to expand their knowledge in the formation of their citizenship. The main goal of this research was to investigate how educational activities planned on the Cultural Heritage may contribute to the understanding of the place of living of the students of the Youth and Adult Education (EJA), from the Public Elementary School Marietta D'Ambrosio in the city of Santa Maria. Thereunto, several educational activities were planned on cultural freeholds around the school, expanding educational activities for the Historical Center of the city of Santa Maria, RS. The specific goals of the survey were: understand the sociocultural reality of the students from EJA; understand how the students from EJA perceive cultural property from educational activities in different locations around the city; analyze how educational activities on local cultural freeholds can contribute to the understanding of the place of living of the students from EJA; identify how heritage education can be addressed in the curriculum of EJA. Based on this assumption, this paper presents some results and thoughts related to this theme from the experiences lived by the students in understanding the questions and proposals according to the objectives of this survey. It was defined as an investigative method the action-survey, developed in three different stages: a) literature review of concepts by authors that theoretically underlie the issue and analysis of existing legislation; b) data collection from secondary sources through analysis of iconographic and textual documents on cultural freeholds under study; c) empirical data collection on the articulation of the cultural heritage of the city through educational activities. The results revealed that for most students the actions of Heritage Education on cultural local freeholds increased their knowledge about the historical places in the city, providing knowledge about many places that they did not know or did not attribute value. Besides having experienced moments of collective living, which marked the educational process in the school, it was observed the emergence of ties to the city where they live, as well as the comprehension of the importance of knowing to attribute value and assign meaning to the different cultures that permeate the collective spaces, in the representation of distinct social groups through the time. It was also gathered some subsidies to promote progress and improvement on the practice of heritage education which can be developed in schools.